MENARI BERSAMA MATEMATIKA: REPRESENTASI GEOMETRI PADA POLA LANTAI TARI KELE - Dharsono, Farhan Maulana; Aripin; Ratningsih, Nani (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This study aims to explore and describe the mathematical concepts contained in the floor patterns of the Kele Dance from Ciamis Regency through an ethnomathematics approach. The main problem in this research is the view that mathematics is a discipline separate from local culture, requiring efforts to uncover the connection between the two as a contextual learning resource. The research method used is qualitative with a critical ethnography approach. Data were collected through participatory observation, in-depth interviews with dance masters, and audiovisual documentation. Data analysis was carried out using data condensation, data display, and drawing conclusions. The results showed that the Kele Dance floor patterns contain various geometric concepts, including geometric transformations in the form of reflection in the "lengkah" and "nandean" movements, and dilation in the "nyiuk di luhur" movement. Additionally, plane geometry concepts such as concentric circles in the "ronggeng gunung" movement, and pentagons were found, as well as one-dimensional geometry in the form of horizontal lines. The conclusion of this study confirms that the Kele Dance is a cultural artifact representing the spatial and logical-mathematical intelligence of the Ciamis people, which can be integrated into culture-based mathematics learning.